ATF3 Within the Interferon Signaling Pathway: A Potential Biomarker for Predicting Pathological Response to Neoadjuvant Chemoimmunotherapy - Chao He; Rui Han; Taiming Zhang; Peng Zhong; Daijuan Huang; Conghua Lu; Yimin Zhang; Jianghua Li; Yuwen Deng; Yong He (Thoracic Cancer)
ABSTRACT Background Neoadjuvant chemoimmunotherapy has achieved high downstaging and pathologic response rates in nonsmall‐cell lung cancer (NSCLC), but outcomes vary significantly. Early identification of beneficiaries remains a challenge. Methods This study analyzed baseline transcriptomic data from 24 NSCLC patients (9 major pathological response [MPR], 15 nonmajor pathological response [NMPR]) treated with neoadjuvant chemoimmunotherapy, sourced from the GEO database. Molecular analyses and immune infiltration analyses were performed using pathologic response as an endpoint. After identifying the interferon signaling subset NeoIGS, we analyzed the relationship between NeoIGS and immune scores, immune cell infiltration, and immunotherapy efficacy. A key gene in NeoIGS was screened by reveiver operating characteristic curve (ROC) analysis. Subsequently, the expression of the key gene was assessed by immunohistochemistry in 53 NSCLC patients receiving neoadjuvant chemoimmunotherapy. Results Interferon signaling pathway expression and CD8+ T‐cell infiltration were higher in the MPR group. NeoIGS predicted pathological response to neoadjuvant chemoimmunotherapy (AUC = 0.926) and also demonstrated predictive value in the ICIs monotherapy cohort. IPS and TIDE scores also confirmed NeoIGS's association with immunotherapy in the TCGA NSCLC dataset. Furthermore, patients with higher NeoIGS scores had more immune cell infiltration and increased expression of ICI targets. ROC analysis identified ATF3 as NeoIGS's key gene. In the clinical cohort, ATF3 outperformed PD‐L1 in predicting pathologic response, with a 90.0% MPR rate in the high‐expression group. Conclusion We established that a subset of interferon signaling pathways, NeoIGS, is closely associated with immunotherapy. Among them, ATF3 is the most critical gene that accurately predicts pathological remission in neoadjuvant chemoimmunotherapy.